DISEASES NURSING STUDENTS MUST KNOW AND THEIR TEACHING IN THERAPEUTICS (Лучшие интеллектуальные исследования, 2025)
Abstract: Understanding common and critical diseases is essential for nursing students to provide effective patient care. This article highlights key diseases nursing students should be familiar with and discusses strategies for teaching these diseases within the framework of therapeutic education.